2022
DOI: 10.3390/antiox11101913
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Baccharis trimera Leaf Extract Suppresses Lipid Accumulation in C. elegans Dependent on Transcription Factor NHR-49

Abstract: Obesity is a global public health problem that is associated with oxidative stress. One of the strategies for the treatment of obesity is the use of drugs; however, these are expensive and have numerous side effects. Therefore, the search for new alternatives is necessary. Baccharis trimera is used in Brazilian folk medicine for the treatment of obesity. Here, B. trimera leaf extract (BT) showed antioxidant activity in seven in vitro tests, and it was not toxic to 3T3 murine fibroblasts or Caenorhabditis elega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…as a slimming tea [ 4 , 5 , 6 , 7 , 8 ]. Moreover, various biological activities have also been described, including antibacterial, antifungal, antiviral, antiprotozoal, anti-inflammatory, cytotoxic, and antioxidant activities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, the genus is known for its aromatic properties and is widely used in the cosmetic and herbal industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…as a slimming tea [ 4 , 5 , 6 , 7 , 8 ]. Moreover, various biological activities have also been described, including antibacterial, antifungal, antiviral, antiprotozoal, anti-inflammatory, cytotoxic, and antioxidant activities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, the genus is known for its aromatic properties and is widely used in the cosmetic and herbal industries.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the genus is known for its aromatic properties and is widely used in the cosmetic and herbal industries. Previous phytochemical studies of the genus reported several classes of natural products, such as cinnamic acid derivatives [ 7 , 8 , 9 , 10 , 11 ], flavonoids [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], terpenoids [ 11 , 15 , 16 ], and volatile oils [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%